UTILISING Zn AND Cu PRODUCT IN THE CORN MEAL SUBSTRATE AT Saccharomyces cerevisiae BIOPROCESS AND ITS IMPLEMENTATION ON INTERNAL QUALITY OF BROILER - Widjastuti, T.; Abun, A.; Destian, A.; Darana, S. (Journal of the Indonesian Tropical Animal Agriculture, 2009)
This research was conducted to find out the effect and optimal percentage of adding Zn and Cuproteinat supplement product of fermentation by Saccharomyces cerevisiae in the ration on internalquality of the broiler. The experiment used 125 broiler day old chicken with a Completely RandomizedDesign. The ration treatments were R0 (control), R1 (99% R0 + 1% supplement Zn and Cu proteinat), R2(98% R0 + 2% supplement Zn and Cu proteinat), R3 (97% R0 + 3% supplement Zn and Cu proteinat) andR4 (96% R0 + 4% supplement Zn and Cu proteinat) where each treatment was repeated five times andeach replication consisted of five broiler chicks. Variable analysis were body cut weight, carcasspercentage, liver relative weight, and the content of cholesterol broiler meat. Conclusion of the researchshowed that by using 3% of Zn and Cu proteinat supplement substrat in the ration gave the best internalquality of broiler, increased body cut weight, carcass percentage, otherwise liver relative weight and thecontent of cholesterol broiler meat were normal.